Dokumentacja Wizytacji Greckokatolickich w Archiwum Obwodowym w Żytomierzu - Wodzianowska, Irena (Archiwa, Biblioteki i Muzea Kościelne, 2012)
In the State Archive of Zhytomyr Oblast there is one of the biggest collections of the visitations of the Greek Catholic parishes in Ukraine. Visitations from the years 1717-1814 territorially include 35 deaneries of eastern territories of the former Polish Republic (now Ukraine, Moldova, Belarus). Scattered in several fonds, the visitation protocols are a record of both canonical visitations and deanery ones. This source enables to characterize socio-religious life of more than 2000 parishes. Those who inspected the parishes noted down not only the name of the parish, to what saints it was dedicated and in which year it was founded, described its appearance and salary but also provided personal details of clergymen and their families. In addition, they presented, in details, the fi nancial security of priests-the fund, mostly in the form of fi elds, meadows, orchards, fi sh ponds and various privileges. You can also fi nd information on the density and structure of the population, customs of parishioners, their religious life, their activity, fraternities connected with Uniate churches, schools and hospitals (treated as points of social welfare for the poor and elderly). The visitation material is an interesting source for the research not only on the changes in the deanery structure and the increase in the number of parishes, but also on the relationships between different faiths and peoples inhabiting this land.